BRCA1/2 MUTATIONS IN PATIENTS WITH HEREDITARY BREAST - OVARIAN CANCER SYNDROME (Vietnam Journal of Community Medicine, 2022)
Individuals with BRCA1/2 gene mutations are at increased risk of breast and ovarian cancer.The prevalence of BRCA1/2 mutations varies by race and ethnicity. The prevalence and the risksassociated with most BRCA1/2 mutations has not been unknown in the Vietnamese population. Weherein screen the entire BRCA1 and BRCA2 genes for breast and ovarian cancer patients withHereditary Breast - Ovarian Cancer Syndrome (HBOC), thereby, suggesting personalizedevaluation risk of mutation carrier, breast and ovarian cancer and personalized plan of cancersscreening and prevention.Objects: 33 patients who had a pathological diagnosis of breast and/or ovarian cancer withHBOC syndrome.Methods: Cross-sectional descriptive. Blood samples of 33 patients were collected andanalyzed using Next Generation Sequencing. The identified mutations were tested by Sangersequencing. Identification of mutations in the family members of patients carrying the mutation.Results: Eleven types of mutations in both BRCA1 (in nine patients) and BRCA2 (in threepatients) were detected, one of which (BRCA2:p.Ser1341Ter) is novel, unpublished. Seven out of19 patient’s relatives had BRCA1/2 gene mutations. All patients were counselled about thelikelihood of cancer rising and prophylactic screening and procedures. Conclusions: Our findingssuggested the implications for the planning of a screening programme for BRCA1 and BRCA2genes testing in breast and ovarian cancer patients and genetic screening in their relatives.
Keywords: BRCA1; BRCA2; UT vú và buồng trứng di truyền.